Application of Combined Laser Irradiation in Postoperative Period in Patients with Complicated Hepatic Echinococcosis - A. R. Babadzhanov; K. B. Babadzhanov; K.J.Matmuratov; I.U.Pulatov; S.Sh.Yakhshibaev (Zien Journals, 2023)
The article presents an analysis of the results of surgical treatment of patients with complicated liver echinococcosis in 102 patients using laser technology in the postoperative period. The patients were divided into 2 groups. Group I 62 (61%) patients with the use of laser technology in the postoperative period. II group 40 (39%) patients with the traditional method. Due to the use of low-energy lasers in the postoperative period with complicated liver echinococcosis, the proportion of complications was reduced by 3-3.5 times, and the duration of inpatient treatment was reduced by 1.5-2 times
Keywords: liver echinococcosis; recurrent echinococcosis; complications